The MOST IMPORTANT STRATEGIC WAYS AFFECTING The ABBASID STATE'S TRADE With OTHER COUNTRIES ) SILK ROAD As A MODEL) - Ali , Venus (Islamic Sciences Journal, 2023)
The Silk Road gained a good reputation and unprecedented fame, as a result of the goods known for its name, which was not only attracted the attention of merchants and travelers, but was the focus of attention of the caliphs, kings and kingdoms through which the convoys of multinational merchants were passing as it was not only a route for silk merchants, but was The Silk Road also played an important role in scientific and economic exchanges. Therefore, the Silk Road is not merely a geography, not a history, not merely an identity. This identity is united by difference, convergence and contrast. Coexistence and peace